Assignment and modelling of 12CH4 spectra in the 5550–5695, 5718–5725 and 5792–5814 cm−1 regions. (November 2018) - Nikitin, A.V.; Thomas, X.; Daumont, L.; Rey, M.; Sung, K.; Toon, G.C.; Smith, M.A.H.; Mantz, A.W.; Protasevich, A.E.; Tashkun, S.A.; Tyuterev, Vl.G.
Highlights: 5819 line positions and intensities were retrieved from measured spectra in the 5550- 5825 cm −1 region. More than 2800 new assignments were made in the region. More than 3445 experimental line positions were modeled to 0.0024 cm −1 . Abstract: A new study of 12 CH4 line positions and intensities was performed for the Tetradecad regions 5550, 000–5695.250, 5718.8–5724.250 and 5792.36–5814.290 cm −1 using long path (202 m, 602 m, 1604 m and 1804 m) spectra of normal samples of CH4 at different pressures recorded with a Fourier transform spectrometer in Reims, France. Line positions and intensities were retrieved by least squares curve-fitting procedures and analyzed using the effective Hamiltonian and the effective dipole moment expressed in terms of irreducible tensor operators adapted to spherical top molecules. An 80 K spectrum recorded in Jet Propulsion Laboratory (JPL), Pasadena, of enriched 12 CH4 was used for low-J line positions. Another 80 K spectrum of enriched 13 CH4 from JPL was used to discern the isotopic lines. A new measured linelist contains positions and intensities for 5819 features. Quantum assignments were made for more than 3400 transitions, which represent ∼95% of the integrated line intensity observed in this region. All assigned 3445 line positions were fitted with RMS standard deviations of 0.0024 cm −1 . The sum of observed intensities between 5550 and 5695 cm −1 fell within 2% of the predicted value from ab initio variational calculations reported in the TheoReTS database (http://theorets.univ-reims.fr ;http://theorets.tsu.ru ).